Whole Cell-based Biosensors for Environmental Heavy Metals Detection - Teo, Siok Chin; Wong, Ling Shing (SCIENCEDOMAIN international, 2014)
Biosensors have emerged as new alternatives in environmental toxicity assessment. In the development of biosensors for heavy metals detection in environment, whole cells are highly favored as these cells are able to reflect the real toxicity effects of heavy metals to living organisms. For heavy metals detection, the integration of several types of cells such as bacteria, cyanobacteria, and algae into biosensors development has been widely reported. The usage of other cells such as plant cell, protozoa, and yeast has been reported as well. Although these biosensors are highly sensitive to heavy metals, the detection is still limited to the heavy metals which are bioavailable to the cells. Besides, the response of whole cells to wide range of heavy metals makes them excellent tools for wide spectrum screening but lack of specificity in detection. Whole cells are living entities with complex biochemical processes, which make the optimization of whole cell-based biosensors a tedious process, while maintaining the stability and storability are still challenging tasks. Although naturally occurring cells are highly favored, some reports show that recombinant cells can be a choice with better performance. In this paper, the usage of whole cells in biosensors for heavy metals detection and some of the current issues which are tied to the development of these biosensors are reviewed.